Dying in a strange land - Murayama, Milton (University of Hawaii Press, 2008)
Milton Murayama's long-awaited Dying in a Strange Land brings to a close the saga of the Oyama family. Familiar faces from All I Asking For Is My Body, Five Years on a Rock, and Plantation Boy return to advance the story from the years immediately following World War II to the 1980s. After her husband sinks them deep in debt, strong-willed and pragmatic Sawa takes charge of the family. The war ends and her children leave the plantation camp for Honolulu and the Mainland, but Sawa has little time for loneliness or regret. When asked by her neighbors if she misses them, she replies, "They must look for what they want."However, Tosh, the eldest--who has long been saddled with the burden of his family's failures in addition to his own--is wise to his mother's "sob stories": "She going hold you to your samurai's word," he warns his brothers. Even after he becomes an architect, Tosh is quick to blame his problems on "oya-koh-koh" (filial piety). Living on the East Coast and unable to make ends meet as a writer, Kiyo, the third son, takes any job that doesn't leave him too word-weary or emotionally exhausted to write in his spare time. Chronic fatigue turns him into a minimalist. At 52 he finally finds acclaim when he publishes a novel about issei and nisei in rural Hawai'i. Not much is expected of Miwa, the fifth child and second daughter. Pregnant at sixteen and forced to leave school, she is rejected by her family and bullied by her in-laws until she finds work as a maid at one of the new hotels in West Maui. A surprise promotion brings Miwa self-esteem and a good income--and respect from her relatives. Just as each generation of the Oyama family struggles to find a way to survive the diaspora from Japan to Hawaii and beyond, so must Sawa, Tosh, Kiyo, and Miwa deal individually with the collision between Japanese and American values, between duty to family and personal freedom